An encounter with the self: A thematic and content analysis of the DMT experience from a naturalistic field study - Michael, Pascal; Luke, David; Robinson, Oliver (Frontiers in Psychology, 2023)
Introduction: N,N-dimethyltryptamine (DMT) is an endogenous serotonergic psychedelic capable of producing radical shifts in experience that have significant implications for consciousness and its neural correlates, especially given the ‘disconnected consciousness’ suggested by the ‘breakthrough’ DMT state. Its increasing usage and clinical trialling indicates the growing importance of a thorough elucidation of the experience’s qualitative content, over and above the phenomenological structure. This is particularly in light of the intensely pervasive effects DMT occasions in all dimensions of the self, which are often ontologically challenging yet potentially transformative. Methods: This is the second report on the first naturalistic field study of DMT use exploring its qualitative analysis. Screened, healthy, anonymised and experienced DMT users were observed during their non-clinical use of the drug at home (40–75 mg inhaled). In-depth semi-structured interviews, inspired by the micro-phenomenological technique, were employed immediately after their experience. This paper reports on the thematic and content analysis of one major domain of the breakthrough experiences elicited, the ‘self’; where analyses of the ‘other’ were previously reported (Michael et al. 2021). Thirty-six post-DMT experience interviews with mostly Caucasian (83%) males (eight female) of mean 37 years were predominantly inductively coded. Results: Invariably, profound and highly intense experiences occurred. The first overarching category comprised the Onset of effects, encompassing super-ordinate themes including Sensory, Emotion & Body, and Space-time shifts; the second category comprised Bodily effects, encompassing themes including Pleasurable, Neutral/Both, and Uncomfortable; the third category comprised the Sensorial effects, encompassing Open-Eye, Visual, and Cross-modal & Other; the fourth comprised the Psychological effects, encompassing Memory & Language, Awareness & Sense of Self, and Time distortions; and the fifth comprised the Emotional effects, encompassing Positive, Neither/Both, and Challenging experiences. Many further subthemes also illuminate the rich content of the DMT experience. Discussion: The present study provides a systematic and nuanced analysis of the content of the breakthrough DMT state pertaining to one’s personal and self-referential experiences of the body, senses, psychology and emotions. The resonances both with previous DMT studies and other types of extraordinary experiences, such as the alien abduction, shamanic and near-death experience are also elaborated upon. Putative neural...